Experimental determination of the plastic deformation and fracture behavior of polypropylene composites under various strain rates - Minsoo Kim (Elsevier, 2021)
A strain measurement method is proposed that defines an intrinsic flow stress equation for various strain rates using representative brittle and ductile polypropylene composites. Digital image correlation is used to track strain at the local fracture point. Results are compared with those of the gauge length method. Whereas the strain up to diffuse necking is identical, regardless of the acquisition method, the strain after diffuse necking is completely dependent on the specimen's fracture location; hence, it is underestimated if the fracture is not in the specimen's center. In brittle material, fracture strain deviation is not large because fracture occurs immediately after necking. In ductile material, limits to extrapolating from the stress–strain relationship before necking exist, as stress-softening progresses slowly. The proposed method reduced the fracture strain deviation to 20% of that of the existing method, thereby determining a consistent and quantitative plastic stress–strain relationship up to fracture.